2014
DOI: 10.1534/g3.114.011445
|View full text |Cite
|
Sign up to set email alerts
|

The I-TevI Nuclease and Linker Domains Contribute to the Specificity of Monomeric TALENs

Abstract: Precise genome editing in complex genomes is enabled by engineered nucleases that can be programmed to cleave in a site-specific manner. Here, we fused the small, sequence-tolerant monomeric nuclease domain from the homing endonuclease I-TevI to transcription-like activator effectors (TALEs) to create monomeric Tev-TALE nucleases (Tev-mTALENs). Using the PthXo1 TALE scaffold to optimize the Tev-mTALEN architecture, we found that choice of the N-terminal fusion point on the TALE greatly influenced activity in y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…The I-TevI nuclease and linker domains have successfully been fused to four different DNA-binding architectures that are used in genome editing: zinc fingers (27), TALEs (29), meganucleases (30), and, as reported here, Cas9. An on-going debate in the genomeediting field centers on the ease of use (targeting range) versus specificity (off-target effects) of the various reagents, particularly for common laboratory manipulations of cell lines or model organisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The I-TevI nuclease and linker domains have successfully been fused to four different DNA-binding architectures that are used in genome editing: zinc fingers (27), TALEs (29), meganucleases (30), and, as reported here, Cas9. An on-going debate in the genomeediting field centers on the ease of use (targeting range) versus specificity (off-target effects) of the various reagents, particularly for common laboratory manipulations of cell lines or model organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that the length of the DNA spacer is crucial for I-TevI cleavage function, with lengths of 14-19 bp supporting activity in various chimeric contexts (27,29,30). We coexpressed TevCas9 with a C-terminal histidine tag and a gRNA targeting a site in the retinoic acid receptor alpha gene (RARA.233, numbered according to start of target site in the RARA cDNA) from the same plasmid in Escherichia coli.…”
Section: Significancementioning
confidence: 99%
“…Engineering nicking enzymes in all kinds of the chimeric artificial nucleases also resulted in a substantial progress of this field [46][47][48][49][50][51][52]. Alternative nuclease domains have been applied in few cases in mainly monomeric chimera [53][54][55][56][57][58] and non-FokI-based zinc finger nucleases have also been developed by introducing mutations or small modifications into the zinc finger array, such as the exchange of the metal ion-binding cysteines to histidines [59][60][61]. Trials to establish controlled artificial nucleases through lightactivation [62,63], DNA binding [64], cold-shock technique [65], protein-protein interaction [66], DNA modification [67] or metal ion dependent DNA binding [68] were also executed.…”
Section: Current Artificial Nucleasesmentioning
confidence: 99%
“…Several groups have attempted to create a hybrid nuclease by fusing TALE DNA domains with monomeric meganucleases, such as I -TevI , I -AniI , and I -OnuI . The resulting nucleases, termed megaTAL or compact TALEN, have shown great potential with high specifi city and activity (Beurdeley et al 2013 ;Kleinstiver et al 2014 ;Boissel et al 2014 ). Because all the meganucleases fused in megaTALs are monomeric endonucleases, the new hybrid nuclease does not require dimerization to cleave target sites.…”
Section: Fusion He-talementioning
confidence: 99%
“…This approach helps expand the collection of meganucleases with distinct target site specifi city for genome engineering applications. The other strategy is to create a hybrid nuclease architecture by combining the TALE DNA binding domain, due to ease of engineering and versatility, with the monomeric nuclease domain from meganucleases (Beurdeley et al 2013 ;Kleinstiver et al 2014 ;Boissel et al 2014 ).…”
Section: Future Perspectivesmentioning
confidence: 99%